The relationship between attitudes toward telework and well-being: the mediating role of interpersonal interactions and the moderating role of neuroticism - Ana Junça-Silva; Leonor Lourenço (Computers in Human Behavior Reports, 2025)
Grounded in the e-work life model, this study examined the relationship between attitudes toward telework and well-being, proposing interpersonal interactions as a mediating mechanism. Furthermore, neuroticism has been identified as a moderating factor that could shape how employees perceive and react to telework. Consequently, this study also tested the moderating role of neuroticism in the relationship between attitudes toward telework and well-being, mediated by interpersonal interactions. To test the model, a three wave-study was conducted (N = 353). The findings revealed that attitudes toward telework were positively associated with well-being through its facilitation of interpersonal interactions. However, this relationship was moderated by neuroticism, being stronger among individuals with lower levels of this personality trait. These results suggest that a positive attitude toward telework plays a crucial role in fostering healthy and cooperative interpersonal relationships among colleagues, which, in turn, enhance well-being. Therefore, workers’ attitudes toward telework may be pivotal in creating a positive work environment that promotes well-being through stronger and more constructive interpersonal dynamics.